Penyuluhan Manajemen Pemilahan Sampah Mandiri di SD Negeri 2 Palembang - Dimitri Yulianti; Lega Reskita Lubis; Rizki Prasetya Person; Yuri Khairizal; Ibrahim Ibrahim (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service Program aims to enhance the awareness, knowledge, and practical skills of teachers and students at SD Negeri 2 Palembang in carrying out independent waste management. The main issue identified was the lack of awareness and discipline in sorting organic and inorganic waste, which contributes to environmental pollution and poor hygiene within the school area. The program was implemented through lectures, interactive discussions, and hands-on training involving the use of separate bins for different waste types. The results demonstrated a remarkable improvement in waste management understanding and behavior. Teachers and students have developed new habits of waste sorting before disposal, resulting in a cleaner, healthier, and more pleasant school environment. Additionally, the activity inspired creativity in transforming inorganic waste into useful and economically valuable crafts that can be reused. Overall, this program fostered environmental awareness, strengthened community participation, and encouraged sustainable waste management practices as part of daily school culture.